From the blackwash dream to the SNI nightmare? A study of the shifting position of black women within a black consciousness movement - Manzi, Ncebakazi (My University, 2019)
This study investigates the gradual marginalisation of Black women in an anti-racist movement founded by Black women. For the purposes of this investigation, nine women who were activists in Blackwash and the September National Imbizo (SNI) between 2008 and 2014 were interviewed. The literature on how women navigate their way through Black nationalist movements suggests that feminist interests are often considered secondary despite women playing a critical role in building such movements. In this study, the immense contribution of women is clear from the movement’s inception and the work traces key developments that result in women losing their place from the centre of the movement. It is argued firstly that the transition from Blackwash to the SNI was a key contributing factor due to the different organisational structures of the two. Secondly, the study indicates that women’s sexual autonomy was undermined in ways that allowed for violent masculinities to take centre stage thus further marginalising women. Finally, the study posits that appropriations of a certain interpretation of Afropessimism consolidated patriarchal power within the movement. At the same time, women’s Black feminist consciousness and practice presented a challenge to the masculinisation of the movement.
Research report submitted for the degree of Master of Arts by Coursework and Research Report in Sociology at Wits University, March 2019
Keywords: Women's rights-South Africa; Social movements-South Africa